Kualitas Pelayanan Kesehatan di Instalasi Gawat Darurat Bagi Pasien pada Rumah Sakit Umum Daerah Cililin Kabupaten Bandung Barat - Asep Asep; Agustina Setiawan; Rira Nuradhawati (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Rumah Sakit Umum Daerah Cililin has not yet achieved patient satisfaction, with ongoing complaints about suboptimal health service quality, particularly in the Emergency Department (IGD). This study aims to identify the causes of inadequate health service quality as observed in the IGD. The research employs a descriptive method with a qualitative approach. Data collection was conducted using observation, interviews, and documentation techniques. The researcher used source triangulation to verify the validity of the data. Data analysis was performed through data reduction, data presentation, and conclusion drawing. This study assessed the quality of health services in the Emergency Department at RSUD Cililin, Kabupaten Bandung Barat, based on six main indicators: 1) Professional and Skill; 2) Attitudes and Behavior; 3) Accessibility and Flexibility; 4) Reliability and Trustworthiness; 5) Recovery; and 6) Reputation and Credibility. The general overview of the identified issues includes: 1) Limited number of certified medical staff; 2) High-pressure work environment; 3) Limited space and equipment; 4) Issues with medical equipment; 5) Slow evaluation processes; and 6) Impact of adverse patient incidents. Overall, the quality of services in the Emergency Department at RSUD Cililin can be considered adequate. Despite facing various challenges, RSUD Cililin demonstrates a strong commitment and effort to improve emergency department services, reflecting dedication to patient welfare and ongoing enhancement of health service quality.